Enhanced ethanol production from sugarcane molasses by industrially engineered Saccharomyces cerevisiae via replacement of the PHO4 gene. Issue 4 (10th January 2020) - Wu, Renzhi; Chen, Dong; Cao, Shuwei; Lu, Zhilong; Huang, Jun; Lu, Qi; Chen, Ying; Chen, Xiaoling; Guan, Ni; Wei, Yutuo; Huang, Ribo
Abstract : Replacement of a novel candidate ethanol fermentation-associated regulatory gene, PHO4, from a fast-growing strain through a novel strategy (SHPERM-bCGHR), is hypothesised to shorten fermentation time and enhance ethanol yield from sugarcane molasses. Abstract : Replacement of a novel candidate ethanol fermentation-associated regulatory gene, PHO4, from a fast-growing strain MC15, as determined through comparative genomics analysis among three yeast strains with significant differences in ethanol yield, is hypothesised to shorten the fermentation time and enhance ethanol production from sugarcane molasses. This study sought to test this hypothesis through a novel strategy involving the transfer of the PHO4 gene from a low ethanol-producing, yet fast-growing strain MC15 to a high ethanol-producing industrial strain MF01 through homologous recombination. The results indicated that PHO4 in the industrially engineered strain MF01-PHO4 displayed genomic stability with a mean maximum ethanol yield that rose to 114.71 g L −1, accounting for a 5.30% increase in ethanol yield and 12.5% decrease in fermentation time in comparison with that in the original strain MF01, which was the current highest ethanol-producing strain in SCM fermentation in the reported literature. These results serve to advance our current understanding of the association between improving ethanol yield and replacement of PHO4, while providing a feasible strategy for industrially engineered yeast strains to improve ethanol production efficiently.